The nociceptive withdrawal reflex during spinal analgesia in pigs undergoing veno-arterial extracorporeal membrane oxygenation: a prospective observational study - Petrucci, Mariafrancesca; Spadavecchia, Claudia; Bachmann, Kaspar F.; Berger, David; Mirra, Alessandro; Casoni, Daniela (Frontiers in Veterinary Science, 2024)
IntroductionUse of veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is still in the focus of research, in which pigs are commonly involved. During VA-ECMO, cardiovascular parameters are artificially manipulated and therefore not reliable indicators of nociception. Nociceptive withdrawal reflex (NWR) thresholds can be a suitable alternative in such a context. This study aimed at recording and comparing NWR thresholds before and after administering spinal analgesia in healthy pigs undergoing VA-ECMO.MethodsSixteen pigs were sedated with a mixture of ketamine, midazolam, and methadone; general anesthesia was induced with propofol and maintained with propofol and fentanyl in continuous rate infusion. Before surgery, ropivacaine 0.75% and morphine (RM) were injected via a spinal catheter (T13-L1). Nociceptive withdrawal reflex thresholds were recorded before RM (baseline) and at 40 min, end of surgery, 240, 300, 360, 420 and 480 min afterward. If after spinal analgesia NWR thresholds increased ≥20% from their baseline values, the increase was deemed clinically relevant. If NWR thresholds decreased at least 20% from their baseline values, ropivacaine alone was injected (rescue analgesia). Thresholds were compared with baseline using ANOVA on Ranks followed by Dunn’s method. At each time point, the number of pigs showing a clinically relevant increase in thresholds, thresholds higher than the maximum stimulation intensity and the need of rescue analgesia, was assessed. Nine animals were included in the final data analysis.ResultsA clinically relevant increase of the thresholds was achieved in all the pigs at 240 min after the injection of RM. A statistically significant increase in NWR thresholds was found at 300 and 360 min (p = 0.009 and 0.048, respectively) compared to baseline. Rescue analgesia was required at 300 (one pig) and 420 (two pigs) and 480 (one pig) minutes.Discussion and conclusionNociceptive withdrawal reflex thresholds increased significantly, both clinically and statistically following spinal injection. Their increase suggests that the combination of spinal morphine and ropivacaine can last on average up to 6 h. Particularly in those scenarios where cardiovascular variables are unreliable, NWR thresholds could be useful for evaluating antinociception following spinal analgesia in pigs.